Jogos no ensino da Matemática Financeira no nível médio - FIGUEIREDO, Luis Carlos Gomes (2024)
This work presents an experience report having the application of mathematical games as a strategy for the teaching and learning of mathematics in the 3º year of High School, at the State School of Elementary and High School João Santos in the city of Capanema-PA in the first semester of 2023. Whose objective was to encourage the use of Mathematical Games in the high school classroom, as a tool that assists in the learning of the contents of Financial Mathematics, offering the student the possibility of learning and with a different perspective from those presented in the classroom. Mathematical games stimulate reasoning and improve elements such as observation, concentration, analysis and attention, which are fundamental to the learning of Mathematics and contribute to the development of logical reasoning (ALMEIDA , 2020, p.85), thus providing students with a way to face and solve situations in a continuous and reflective process that can facilitate the learning of mathematics. As a result, we found that the students showed more interest in the content of Financial Mathematics and were able to contextualize the mathematical content with situations they experience in their daily lives.